2015
DOI: 10.5539/mas.v9n13p44
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning, Characterization, and Expression Analysis of DROOPING LEAF gene in the Pistillody Line of Common Wheat

Abstract: <p class="NewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNewNew">In this article, we report the cloning, characterization, and expression pattern of <em>Triticum aestivum DROOPING LEAF</em> gene (<em>TaDL</em>) in pistillody line of common wheat. Three <em>TaDL</em> homoeologous genes (<em>TaDL1</em>, <em>TaDL2</em>, and <em>TaDL3&l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The YABBY genes constitute a small transcription factor family characterized by two conserved domains, an N-terminal region C2C2 zinc-finger domain and a C-region YABBY domain [ 7 ]. To examine the structural features of 55 YABBY proteins, multiple sequence alignments analysis of magnoliids YABBY proteins were applied to generate sequence logos of both the C2C2 zinc-finger and YABBY domains in seven magnoliids and Arabidopsis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The YABBY genes constitute a small transcription factor family characterized by two conserved domains, an N-terminal region C2C2 zinc-finger domain and a C-region YABBY domain [ 7 ]. To examine the structural features of 55 YABBY proteins, multiple sequence alignments analysis of magnoliids YABBY proteins were applied to generate sequence logos of both the C2C2 zinc-finger and YABBY domains in seven magnoliids and Arabidopsis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike other transcription factor families, YABBY genes seemed to be absent in non-seed lineages of embryophyte plants [ 5 ]. Additionally, YABBY genes encode putative transcription factors that consist of a zinc-finger domain in the N-terminal and C-terminal YABBY domain, similar to a high-mobility group (HMG) box [ 6 , 7 ]. In Arabidopsis thaliana , the YABBY gene family has a distinct role, declared to six subclades, including CRABS CLAW ( CRC ), INNER NO OUTER ( INO ), FILAMENTOUS FLOWER ( FIL ), YABBY3 ( YAB3 ), YABBY2 ( YAB2 ), and YABBY5 ( YAB5 ) [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factors play an important role in regulating the development of plants. Some previous studies have reported that MADS-box [9,14,16,17,26,27,28] and DROOPING LEAF gene of YABBY family [6,15,16] associated with the development of wheat pistillody-stamen. We identify MADS-box and YABBY transcription factors from wheat flower substructure tissues (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 4 published YABBY transcription factors are considered to regulate the development of wheat pistiilosy-stamen [6,15,16]. The published 4 proteins of YABBY have been aligned with the 15 180 floral proteins of Additional file 1: Table S1 by BLAST.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation